Investigating Adult Education for Immigrants in South Korea - Jihyun Kim; Thomas Valentine (Adult Education Research Conference, 2014)
This session (a) describes current practices in adult education for immigrants in South Korea and (b) seeks to collaboratively develop a research agenda for those interested in investigating the role of adult education research in supporting the individual and societal adaptations necessary for supporting multiculturalism in a society once characterized by homogeneity of cultural and strong social cohesion.